Gut microbiome homeostasis and the future of probiotics in cancer immunotherapy - Singh, Ankita; Alexander, Sharon Grace; Martin, Sunil (Frontiers in Immunology, 2023)
The gut microbiome has an impact on cancer immune surveillance and immunotherapy, with recent studies showing categorical differences between immunotherapy-sensitive and immunotherapy-resistant cancer patient cohorts. Although probiotics are traditionally being supplemented to promote treatments or sustain therapeutic benefits; the FDA has not approved any for use with immunotherapy. The first step in developing probiotics for immunotherapy is identifying helpful or harmful bacteria down to the strain level. The gut microbiome's heterogeneity before and during treatment is also being investigated to determine microbial strains that are important for immunotherapy. Moreover, Dietary fiber intake, prebiotic supplementation, and fecal microbiota transplantation (FMT) were found to enhance intratumoral CD8+ T cell to T-reg ratio in the clinics. The possibility of probiotic immunotherapy as a "living adjuvant" to CAR treatment and checkpoint blockade resistance is actively being investigated.